Integrating Real-Time Main Controller with Power Prediction Interface and State Classifier in Energy Harvesting Systems: An Approach - Xavier, Jozimar C.; Spengler, Anderson W. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2023: Anais do XIII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2023)
Embedded systems with energy harvesting capabilities present an intriguing solution for demanding scenarios where prolonged operation is required, and replacing or replenishing the energy storage unit with a power supply is not feasible. Therefore, effective management of both consumed and generated energy becomes crucial, given the dynamic behavior of applications utilizing such systems. Based on these scenarios, the proposed approach integrates power management and saving techniques into an embedded system that utilizes energy harvesting resources. These techniques include a strategy for executing system tasks while considering energy and time constraints, as well as the utilization of a state classifier to switch the system’s overall operating mode. The approach is analyzed within a specific scenario where the embedded system functions as a sensor node, dedicated to the exploration and monitoring of oil and gas reservoirs. The results obtained from this analysis showcase the approach’s promising potential in extending the system’s lifetime while effectively managing the demands of hard real-time tasks.